2007
DOI: 10.1177/1077800406294947
|View full text |Cite
|
Sign up to set email alerts
|

Telling Secrets, Revealing Lives

Abstract: This article focuses on relational ethics in research with intimate others. Relational ethics requires researchers to act from our hearts and minds, acknowledge our interpersonal bonds to others, and take responsibility for actions and their consequences. Calling on her own research studies, the author examines relational ethics in ethnographies in which researchers are friends with or become friends with participants over the course of their projects. Then she examines autoethnographic narratives in which res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
243
0
9

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 788 publications
(254 citation statements)
references
References 28 publications
2
243
0
9
Order By: Relevance
“…As trust is (ideally) built, we have observed in our cases situations in which a researcher's identity might be clear upfront but can fade into the background over time, for example, when a researcher or research advisor ends up taking on a significant participatory project manager and facilitator role (e.g., cases 6, 7, and 8). Some researchers such as Ellis (2007) describe this change as a potential pitfall of long-term engagement with participants, but we can also see it as a strength of applied and reflexive research in which researchers have the option of a fluidity of role to support and broker effective research-practice in collaboration with communities and stakeholders over time.…”
Section: Coimplementation: the Dilemmas Of Doing Ethical Researchpracmentioning
confidence: 99%
See 2 more Smart Citations
“…As trust is (ideally) built, we have observed in our cases situations in which a researcher's identity might be clear upfront but can fade into the background over time, for example, when a researcher or research advisor ends up taking on a significant participatory project manager and facilitator role (e.g., cases 6, 7, and 8). Some researchers such as Ellis (2007) describe this change as a potential pitfall of long-term engagement with participants, but we can also see it as a strength of applied and reflexive research in which researchers have the option of a fluidity of role to support and broker effective research-practice in collaboration with communities and stakeholders over time.…”
Section: Coimplementation: the Dilemmas Of Doing Ethical Researchpracmentioning
confidence: 99%
“…Other scholars have identified that in situations in which professional ethics (such as those involved in funding or research codes of practice) and community norms intersect such as in collaborative research, different values are at play, and therefore, ethical framings can be fraught and contested (see Pradhan andMeinzen-Dick 2003, Orlove andCaton 2010). Ellis (2007) adds a third dimension of "relational ethics" to Guillemin and Gillam's (2004) two categories, which draws attention to the interpersonal bonds formed between researchers and participants. This is particularly relevant in the context of long-term collaborative research partnerships, where the lines between researchers and participants can be blurred when the focus is on managing natural resources such as water.…”
Section: Background To Ethics In Collaborative Research-practicementioning
confidence: 99%
See 1 more Smart Citation
“…It is important to be aware o f the potential for exploiting others and to consider whether or how people are better off as a result of the study. As I write this, I wonder if what I have to write about could possibly be o f such worth but Ellis (2007) reminds me that stories offer the gift of companionship when others might feel alone. I think that is a worthwhile gift; it has been for me.…”
Section: Ethical Concernsmentioning
confidence: 99%
“…For instance, quantitative methods do not tell the reader about the individual lives behind the data. Furthermore, these approaches have been criticized as potentially "sterile" and insensitive to relational ties (Ellis, Adams, & Bochner, 2011, p.2;Ellis, 2007).…”
Section: Qualitative Introductionmentioning
confidence: 99%